Hubungan Pola Asuh Orang Tua dan Motivasi Belajar dengan Hasil Belajar Matematika Siswa Kelas VIII SMP Muhammadiyah Palangka Raya: Hubungan Pola Asuh Orang Tua dan Motivasi Belajar dengan Hasil Belajar Matematika Siswa Kelas VIII SMP Muhammadiyah Palangka Raya - Yumeri; Ardo Subagjo; Sugiharto (JURNAL PENDIDIKAN, 2022)
The results of learning mathematics in class VIII SMP Muhammadiyah Palangka Raya have not yet reached the KKM. Parenting patterns and learning motivation are thought to be correlated as causative factors. This study aims to test the alleged relationship between parenting and learning motivation with mathematics learning outcomes, both individually and interactively. This study uses a quantitative approach to the type of correlational research. The population in this study was 161 students of class VIII SMP Muhammadiyah Palangka Raya. A sample of 127 students was selected using the Simple Random Sampling technique. The instruments used in this study were a parenting questionnaire (( = 0.92), learning motivation (( = 0.94) and a mathematics learning achievement test (( = 0.85). Data were analyzed by calculating the average value, and standard deviation, and testing the hypothesis with Spearman's correlation analysis at a significant level ∝= 0.05. The results of hypothesis testing show that there is a significant positive relationship between parenting styles and students' mathematics learning outcomes (( 0,20) 0.20); learning motivation with students' mathematics learning outcomes (( 0,20), and there is a significant positive relationship between parenting and learning motivation with mathematics learning outcomes (=0.28)